2016
DOI: 10.1115/1.4030534
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Solution of Fractional Order Diffusivity Equation With Wellbore Storage and Skin Effects

Abstract: This paper addresses the model, solution and analysis of fluid flow behavior in fractal reservoirs considering Wellbore Storage and Skin Effects (WS-SE). In the light of the fractional calculus (FC), the general form of fluid flow model considering the history of flow in all stages of production is presented. On the basis of Bessel functions theory, analytical solutions in the Laplace transform domain under three outer-boundary conditions, assuming the well is producing at a constant rate, are obtained. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Due to the irregular characteristics of formation, flow of fluid is uneven (fluid is uniform only in ideal cases). To solve this problem, Chang and Yortsos (1990) first applied the frac-tal theory (Mandebort 1982) to actual reservoir, they established a fractal reservoir seepage model and obtained its solution, which provided a theoretical basis for further exploration of fractal reservoir. Aprilian et al (1993) found using the fractal theory to study some traditional reservoirs, the results would be much closer to real situation of reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the irregular characteristics of formation, flow of fluid is uneven (fluid is uniform only in ideal cases). To solve this problem, Chang and Yortsos (1990) first applied the frac-tal theory (Mandebort 1982) to actual reservoir, they established a fractal reservoir seepage model and obtained its solution, which provided a theoretical basis for further exploration of fractal reservoir. Aprilian et al (1993) found using the fractal theory to study some traditional reservoirs, the results would be much closer to real situation of reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…In now a days, fractional order derivatives and integrals have found a very pivotal role in different directions of real world problems [4,16,22,25,26,31,32]. Many physical and engineering problems can be narrated with the help of mathematical model that involve fractional PDEs, like that diffusion and wave equations [29], fractional heat-like and wave-like equations having variable coefficients [2,23,24,33], diffusivity equation possessing wellbore storage and skin effects of fractional order [28], fractional Bagley-Torvik equation [11], fractional model of differential-difference equation [14], chemical kinetics system involving a fractional derivative with Mittag-Leffler kernel [30], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Fractional derivatives and integrals have been gaining more and more interest of scientists due to their extensive applications in different directions of science, social science, engineering and finance [1][2][3][4][5][6][7][8][9] when the relaxation process have to accounted for. In this context, Atangana [10] analyzed the fractional non-linear Fisher's reaction-diffusion equation associated with Caputo-Fabrizio (CF) fractional derivative.…”
Section: Introduction Definitions and Preliminariesmentioning
confidence: 99%